The contribution of transgenic and nontransgenic animal models in Alzheimer's disease drug research and development. Issue 2 (April 2017) - Mhillaj, Emanuela; Cuomo, Vincenzo; Mancuso, Cesare
Abstract : Over the last few years, several papers have become available in the literature on both the main hallmarks of Alzheimer's disease (AD) and the several intracellular pathways whose alteration is responsible for its onset and progression. The use of transgenic and nontransgenic animal models has played a key role in achieving such a remarkable amount of preclinical data, allowing researchers to dissect the cellular changes occurring in the AD brain. In addition, the huge amount of preclinical evidence arising from these animal models was necessary for the further clinical development of pharmacological agents capable of interfering with most of the impaired neural pathways in AD patients. In this respect, a significant role is played by the dysfunction of excitatory and inhibitory neurotransmission responsible for the cognitive and behavioral symptoms described in AD patients. The aim of this review is to summarize the main animal models that contributed toward unraveling the pathological changes in neurotransmitter synthesis, release, and receptor binding in AD preclinical studies. The review also provides an updated description of the current pharmacological agents – still under clinical development – acting on the neurotransmitter systems.